Africa's railway renaissance and sustainability: Current knowledge, challenges, and prospects. (January 2023) - Bouraima, Mouhamed Bayane; Alimo, Philip Kofi; Agyeman, Stephen; Sumo, Peter Davis; Lartey-Young, George; Ehebrecht, Daniel; Qiu, Yanjun
Abstract: To fully harness the economic benefits and regional connectivity across the African continent, a sprout in railway redevelopment has been witnessed in recent years. However, there is no study showing the challenges, economic prospects, and knowledge gaps characterizing railway services in Africa. Given that several countries are redeveloping and planning their railway infrastructure, it is necessary to review the existing literature to identify research and policy gaps that African railway transportation planners and their development partners need to take into consideration. Therefore, this systematic literature review analyzed railway-related papers from Africa to determine the current knowledge of the railway network, challenges, economic prospects, and environmental sustainability. The review involved 49 peer-reviewed papers published between January 2000 and June 2022 as well as two recent World Bank reports on railway transportation in Africa. Results showed low penetration of electric-powered trains, technology integration, and shuttle services. Passenger demand, price optimization, route scheduling problems, and transport emission experimentation remain knowledge gaps. The impact of railway projects on wildlife protection and land cover changes would require more empirical studies. The review showed that past studies excluded reflections on policies, regulation, planning, and the opportunities and challenges that come with policy interventions. Prospects realization strategies, including railway training factories, regional implementation of standard gauge railway, and proactive regional action plans have been identified. This study contributes a knowledge map and recommends research gaps that researchers can investigate to strengthen railway management and redevelopment across Africa. Highlights: This study reviewed literature on railway transportation and operation in Africa. There is low integration of electric-powered trains, technology, and shuttle services. Research on policies, regulation, their related opportunities and challenges is lacking. Passenger demand, price optimization, and route scheduling problems are lacking. No CO2 emission and experimentation study was found in the literature.